FEMINISM AND DECONSTRUCTION - MS EN ABYME; DIANE ELAM (NEW YORK ROUTLEDGE, 1994)
Essential reading for anyone who needs an accessible but stimulating guide to the relationship between feminism and deconstruction. A clear and stimulating guide through one of the mazes of contemporary theory.
Keywords: Feminism -- Feminist Theory -- Deconstruction